Novel insights into a reputably irreversible process: combined mRNA and miRNA profiling of tissue from vesicourethral anastomotic stenosis after radical prostatectomy - Worst, Thomas; Daskalova, Kristina; Steidler, Annette; Berner-Leischner, Karin; Röth, Ralph; Niesler, Beate; Weis, Cleo-Aron Thias; Kriegmair, Maximilian; Erben, Philipp; Pfalzgraf, Daniel Philipp (World journal of urology, 2017)
PurposeUntil recently, tissue fibrosis—ultimately leading to permanent scaring—has been considered an irreversible process. However, recent findings indicate that it may be reversible after all. Vesicourethral anastomotic stenosis (VUAS) as fibrous narrowing is a frequent complication after radical prostatectomy with high recurrence rates and requires invasive treatment. The pathophysiology is poorly understood. Therefore, a combined mRNA and miRNA transcription profiling in tissue from VUAS was performed using nCounter technology.MethodsTo assess tissue morphology and fiber composition, histochemical staining was performed. RNA expression of healthy and fibrotic tissue of twelve patients was analyzed using the human miRNA panel v3 and mRNA PanCancer pathway panel on the nCounter gene1 system and qRT-PCR. Differential expression data analysis was performed using the nSolver software implementing the R-based advanced pathway analysis tool. miRWalk2.0 was used for miRNA target prediction.ResultsMore linearized tissue architecture, increased collagens, and decreased elastic fibers were observed in VUAS samples. 23 miRNAs and 118 protein coding genes were differentially expressed (p < 0.01) in fibrotic tissue. miRNA target prediction and overlap analysis indicated an interaction of the strongest deregulated miRNAs with 29 deregulated mRNAs. Pathway analysis revealed alterations in DNA repair, cell cycle regulation, and TGF-beta signaling. qRT-PCR confirmed differential expression of top deregulated miRNAs and mRNAs.ConclusionsIn VUAS tissue, severe alterations on mRNA and miRNA level are found. These consistent changes give insights into the pathogenesis of VUAS after radical prostatectomy and point to future options for transcriptomics-based risk stratification and targeted therapies.
Gesehen am 16.08.2018